KAJIAN SKALA PRODUKSI DAN PENGELOLAAN BIAYA SEBAGAI DASAR EVALUASI KINERJA PADA AGRIBISNIS PEMINDANGAN IKAN LAUT DI DUSUN PAYANGAN WATU-ULO SUMBEREJO KECAMATAN AMBULU - Amien Pudjanarso (RELASI : JURNAL EKONOMI, 2016)
Preserved sea-fish is one of the many seafood products that have been accepted by the community members. This research was intended to analyze the  measure the cost efficiency caused by the allocation of resources in the production process, the breakeven point and to set strategies for developing agribusiness of preserved sea-fish by  through the approaches of Descriptive Analysis,  Benefit Cost Ratio, Profitability Ratio and  Breakeven Point  Analysis. The research results showed that there had been a positive that is, an average of IDR 1,353.00 per kilogram, a profit ratio of more than one (1); that is, 1.50 per kilogram on average, benefit ratio of 33,29% per kilogram on average, breakeven point in sales/production of 21 kg on average, cost and revenue of IDR 202,494,12. Development strategy for sea-fish preservation business should be focused on the improvement of internal management of the company.